2020
DOI: 10.3390/nano10112262
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Toxicity of ZnO Nanoparticles on Scenedesmus rubescens Cultivated in Semi-Batch Mode

Abstract: The scope of this study was to investigate the toxic effects of zinc oxide (ZnO) nanoparticles (NPs) on freshwater microalgae, in long-term semi-batch feeding mode at two different hydraulic retention times (HRTs) (20 and 40 days). A freshwater microalgae, Scenedesmus rubescens, was employed and exposed to a semi-continuous supply of ZnO NPs at a low concentration of 0.081 mg/L for a period of 28 d. Experiments were conducted under controlled environmental conditions. Τhe impact of ZnO NPs on S. rubescens, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Nitrates are a vital compound for cell growth since microalgae are not capable of assimilating the atmospheric or dissolved nitrogen and thus rely on inorganic or organic nitrogen, an element that is crucial for biomass production [6]. On the other hand, it has been found that the increase in nitrate concentration is not always analogous to the biomass concentration [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrates are a vital compound for cell growth since microalgae are not capable of assimilating the atmospheric or dissolved nitrogen and thus rely on inorganic or organic nitrogen, an element that is crucial for biomass production [6]. On the other hand, it has been found that the increase in nitrate concentration is not always analogous to the biomass concentration [7].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, many researchers have been interested in determining the toxic effect of nanoparticles on living organisms and especially on microalgae that form the basis of the food chain on the planet [7,9,13,17]. The results of these studies showed that the type of nanoparticles [13], morphology, concentration, and exposure time [7,9,17], as well as the species of microalgae that were exposed, determined the effect of NPs. In the shortterm toxicity of NPs on microalgae, besides the algal species, an important factor is the cultivation medium that is provided to microalgae during their exposure to NPs [17].…”
Section: Introductionmentioning
confidence: 99%
“…The restrictive influence of V 2 O 5 NPs on the growth of alga in a concentration and time dependent manner was in agreement with some previous findings. The undesirable impact of different transition metal oxide NPs on the growth criteria of plants and algae has previously been reported (Aravantinou et al 2020;Cardinale et al 2012;Khan et al 2021). The lessening in cell number and fresh weight of the algal cell after treatment with metal oxide NPs, such as V 2 O 5 NPs, may occur due to their harm to the cell membrane (Ozkaleli et al 2018;Xia et al 2015), inhibiting the photosynthesis by adsorption of NPs on the algal cell wall and shading effect (Chen et al 2018;Navarro et al 2008) and intracellular damages by the formation of reactive oxygen species (ROS) caused by NPs .…”
Section: Discussionmentioning
confidence: 95%
“…(2017) Zn (92) 150 C. vulgaris - 36.875 333.33 Sibi et al. (2017) ZnO (50–70) 0.081 S. rubescens - - 27.27 Aravantinou et al. (2020) Se (100) 0.4–4 C. vulgaris 40–45 - - Mykhaylenko and Zolotareva.…”
Section: Impacts Of Nanoparticles On Microalgae Speciesmentioning
confidence: 99%